2010
DOI: 10.1002/chir.20824
|View full text |Cite
|
Sign up to set email alerts
|

Determination of catechin diastereomers from the leaves of Byrsonima species using chiral HPLC‐PAD‐CD

Abstract: When catechins are found in plant extracts, they are almost always identified as catechin and/or epicatechin probably due to stereoselectivity of the enzymes involved in the biosynthesis of these substances. However, the lack of reports regarding to ent-catechin as well as ent-epicatechin does not necessarily mean that these compounds have not been produced. In fact, most of the previous reports used chromatographic conditions not suitable for such separation. This article describes a simple and reliable analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
5
30
0
2
Order By: Relevance
“…In addition to the monomeric flavan-3-ols found in MBI, oligomeric proanthocyanidins were suggested as the broad unresolved peak that eluted in the R t range of 35-60 min. This result is in accordance with those obtained by Rinaldo et al (2010), who compared the methanolic extract and infusible form from the leaves of Byrsonima intermedia. The extraction with methanol instead of water did not show any selectivity in the extraction process; however, the concentration of (+)-catechin and (−)-epicathechin was lower in the infusible form.…”
Section: Resultssupporting
confidence: 94%
“…In addition to the monomeric flavan-3-ols found in MBI, oligomeric proanthocyanidins were suggested as the broad unresolved peak that eluted in the R t range of 35-60 min. This result is in accordance with those obtained by Rinaldo et al (2010), who compared the methanolic extract and infusible form from the leaves of Byrsonima intermedia. The extraction with methanol instead of water did not show any selectivity in the extraction process; however, the concentration of (+)-catechin and (−)-epicathechin was lower in the infusible form.…”
Section: Resultssupporting
confidence: 94%
“…They are popularly known as “murici-vermelho” or “murici-cascudo” and grow wild in the cerrado (savannah-like) vegetation of Brazil. Byrsonima species have been scientifically proven to possess several pharmacological properties, such as antiulcerogenic, mutagenic and antimicrobial activity [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Rinaldo et al [14] demonstrated that in MeOH extracts and aqueous infusions from the leaves of five Byrsonima species, only in B. coccolobifolia was it not possible to observe the presence of catechins and epicatechins. In the other four species analyzed, it was found that the MeOH extracts showed larger amounts of catechins than the infusions, per gram of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, separation of enantiomer or diastereoisomer compounds can be accomplished using chiral stationary phases (CSPs) or the addition of chiral additives to the mobile phase on conventional stationary phases. CSPs have been mainly used for the enantiomeric separation of flavanones (Yañez et al, 2007), although chiral HPLC has been also applied for the separation of catechin diastereomers (Rinaldo et al, 2010) or taxifolin enantiomers (Vega-Villa et al, 2009). Chiral additives have been used to separate flavonoid enantiomers mainly by capillary electrophoresis (Cao, Qu, and Cheng, 2010;Kwon and Jung, 2011).…”
Section: Chiral Separationsmentioning
confidence: 99%